Relationship between perineal body length and the occurrence of perineal lacerations in low risk primigravidae: a prospective observational study - Ganiga, Pradeep; Sharma, Ritu A.; Pitty, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Birth canal lacerations include the injuries to cervix, vagina or perineum. Those of the perineum often follow vaginal delivery, and most are first-and second-degree lacerations. Third- and fourth- degree lacerations are considered Obstetrical anal sphincter injuries (OASIS), and their combined incidence varies from 0.5-5%. Risk factors for these more complex perineal injuries have been studied. One important risk factor includes the length of the perineal body which plays an important role in determining the degree of perineal tears. The aim of the study was to assess the relationship between perineal body length and other characteristics, and occurrence of perineal lacerations during delivery in low risk primigravidae in an institution which advocates routine episiotomy for primigravidae. Methods: This was a prospective observational study carried out in the department of obstetrics and gynaecology at AJ Institute of medical sciences among primigravidae who met the selection criteria and delivered between September 2021 and November 2021. A total of 80 women were recruited in this study. In this study, we measured the perineal body length at rest, while the patient was in a dorsal lithotomy position during 1st stage of labor, after delivery the new born’s weight and head circumference were noted. The duration of second stage was noted. These parameters were studied in relation to the occurrence of perineal lacerations and the data was analysed. Results: In the present study it was noted that 10 participants (12.50%) had 3rd degree perineal tears and none had 4th degree perineal tears. With the perineal body length cut off of 3 cm, the sensitivity to predict 3rd and 4th degree perineal tears were found to be 80%, specificity of 90%, positive predictive value of 53.33% and a negative predictive value of 96.92%. The study concluded that a shorter perineal body length, was associated with the occurrence of a 3rd or 4th degree tear, p value of less than 0.00001. The study also showed increased incidence of higher degree perineal tears with higher birth weight and head circumference of the newborn with p value of 0.015 and 0.02 respectively. Conclusions: It can be concluded that Perineal body length of less than 3 cm, higher birth weight and head circumference is associated with an increased incidence of higher order perineal tears. Perineal body length hence has a good ability to predict the occurrence of perineal tears.